“Our classroom methodological prescriptions do not fit easily the problems of studying the SS and their doings”: Elmer Luchterhand and sociological research on Nazi concentration camps - Kranebitter, Andreas (Serendipities. Journal for the Sociology and History of the Social Sciences, 2017)
In the on-going debate about sociology and National Socialism, publications focused on the history of sociology in National Socialism. Sociologists who dealt with National Socialism have not received as much attention. Based on archival material, the work of sociologist Elmer Luchterhand (1911–1996), who took part in the liberation of Hersbruck concentration camp as an US Army officer, will be portrayed and put into the context of other early research. Even though Luchterhand dedicated much of his professional career to the study of Nazi concentration camps, his work remained largely unpublished. It will be argued that the difficulties he faced were substantially related to methodological concerns. Aware ‘classroom methodological prescriptions’ provided little instruction, Luchterhand grappled constantly with an unrewarded search for the ‘right’ way to research genocide.